A Study on Analyzing Side-Channel Resistant Encoding Schemes with Respect to Fault Attacks - Breier, Jakub (2018)
Recently, several software encoding countermeasures were proposed, utilizing the side-channel hiding concept for software implementations. While these schemes aim to protect the underlying code against various leakage models, they can also be utilized against fault injection attacks to some extent. This property comes from the data redundancy that is being employed in order to equalize the leakage. In this work, we analyze three different software encoding schemes with respect to fault injection attacks. We use a custom-made code analyzer to check the vulnerabilities in the assembly code, and we experimentally support our results using laser fault injection technique. Our results show that implementations based on table lookup operations provide reasonable security margin and thwart fault propagation.